Cu(II)-catalyzed synthesis of 2, 4, 5-trisubstituted oxazoles. (21st December 2022) - Prashanth, S.; Adarsh, D.R.; Bantu, Rajashaker; Sridhar, Balasubramanian; Reddy, B.V. Subba
Graphical abstract: Highlights: Reports the synthesis of a highly 2, 4, 5-trisubstituted oxazoles. Coupling of α-diazoketones with aryl or alkyl nitriles. Scope is well exemplified with aroyl and cyclic diazoketones. First report on the coupling of α-diazoketones with aryl or alkyl nitriles. Abstract: A copper catalyzed simple and efficient protocol for the synthesis of 2, 4, 5-trisubstituted oxazoles has been developed from the direct coupling of α-diazoketones with aryl or alkyl nitriles. The reaction proceeds through the formation of nitrilium ion by the nucleophic addition of nitrile onto diazo functionality followed by an intramolecular trapping of nitrilium ion by keto group. Both aryl, and alkyl nitriles underwent smooth cyclocondensation with diazo compounds to afford the trisubstituted oxazoles in excellent yields.